2020
DOI: 10.1111/jgs.16456
|View full text |Cite
|
Sign up to set email alerts
|

Re: Prospective Associations between Diffusion Tensor Imaging Parameters and Frailty in Older Adults

Abstract: See related article by https://doi.org/10.1111/jgs.16343

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 1 publication
1
5
0
Order By: Relevance
“…We further identified the body of corpus callosum being strongly associated with frailty status. We also observed a trend in superior frontooccipital fasciculus, which is in line with previous findings (19). Notably, two previous DTI studies using tract-based spatial statistics report other DTI parameters, such as axial diffusivity (AD) and mean diffusivity (MD) of the anterior limb of internal capsule and superior corona radiata, differ by frailty status.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…We further identified the body of corpus callosum being strongly associated with frailty status. We also observed a trend in superior frontooccipital fasciculus, which is in line with previous findings (19). Notably, two previous DTI studies using tract-based spatial statistics report other DTI parameters, such as axial diffusivity (AD) and mean diffusivity (MD) of the anterior limb of internal capsule and superior corona radiata, differ by frailty status.…”
Section: Discussionsupporting
confidence: 92%
“…Diffusion tensor imaging (DTI)-based brain microstructural measures may be sensitive to subtle age-related and vascular disease-related changes (16,17) and can be used to monitor vascular disease progression (17). To date, only two DTI studies examined white matter microstructural characteristics with frailty (18,19). These studies had relatively small samples and did not examine the microstructure of gray matter.…”
Section: Introductionmentioning
confidence: 99%
“…Artifact-free epochs were band-pass filtered in the following bands of interest: alpha mu [8][9][10][11][12][13] Hz, low beta [12][13][14][15][16][17][18][19][20] Hz, and upper beta [20][21][22][23][24][25][26][27][28][29][30] Hz. Preceding the filtering, the epochs were padded with 2 s (2,000 samples) of real signal on both ends to avoid edge effects within the data.…”
Section: Source Reconstructionmentioning
confidence: 99%
“…The aim of the present work was to investigate the existence of FC abnormalities within brain networks and structures involved in different aspects of motor function that might be affected in frail individuals. We used magnetoencephalography (MEG) to examine FC in the beta [12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30] Hz and alpha mu [8][9][10][11][12][13] Hz frequency bands, given the explicit association between those ranges of oscillation and sensorimotor function (29,30). We hypothesized (1) that FC should be altered in frail individuals when compared to their robust counterparts in the abovementioned RSNs and ROIs, and (2) that MEG is a useful tool to assess brain alterations in cohorts of cognitively healthy frail individuals.…”
Section: Introductionmentioning
confidence: 99%
“…However, in older adults, the evidence as to how frailty affects brain neuroimaging biomarkers is scarce and studies to date offer potentially contradictory results. On the one hand, with the frailty phenotype (FP) some authors found affectation of the brain microstructure (both gray and white matter; Maltais et al, 2020;Tian et al, 2020), with one study only finding association between the slowness component and cortex volume (Nishita et al, 2019). On the other hand, other authors using a 54-item FI that included the execution of instrumental activities (e.g., dressing, using the remote), chronic diseases (e.g., cardiovascular, malignancy) and sensory deficits (e.g., vision and hearing) did not find a relationship with white or gray matter volumes (Jordan et al, 2021).…”
Section: Introductionmentioning
confidence: 99%